Impacts of gasoline aromatic and ethanol levels on the emissions from GDI vehicles: Part 2. Influence on particulate matter, black carbon, and nanoparticle emissions. (15th September 2019) - Yang, Jiacheng; Roth, Patrick; Zhu, Hanwei; Durbin, Thomas D.; Karavalakis, Georgios
Highlights: Gasoline aromatics and ethanol levels will significantly affect particulate emissions. Increases in C9/C10+ aromatics will lead to higher PM emissions. High PMI fuels with higher ethanol blending will result in PM increases. Higher aromatic fuels will cause higher populations of accumulation (soot) particles. Overall, splash-blends showed lower PM emissions than match-blends in GDI exhaust. Abstract: Fuel composition plays an important role on the particulate matter (PM) emissions formation from gasoline direct injection (GDI) engines. In this study, the impacts of gasoline chemical structure and physical properties on the particulate emissions were assessed for a fleet of five Tier 3 compliant GDI vehicles. All vehicles were tested on eight fuels with varying aromatic and ethanol levels, as well as varying PM indices (PMIs) over the LA92 test cycle in at least duplicate on each of the test fuels. Our results showed strong, statistically significant fuel differences for the weighted PM mass emissions and all three phases of the LA92 cycle. The higher aromatic content fuels showed increases in PM mass and black carbon emissions that were statistically significant compared to the lower aromatic fuels. The fuels with higher PMIs showed an upward, but not statistically significant, trend for PM mass emissions with increasing ethanol content likely due to ethanol's evaporative charge cooling effect. This observation does not hold true for the lower PMI fuels. Similar trends to the weighted PM mass emissions were also seen for the cold-start and hot-running PM mass emissions, as well as for the weighted black carbon emissions, indicating a possible ethanol reinforcing effect on PM formation for the high PMI fuels. Total and solid particle number emissions also showed increases with the higher aromatic fuels compared to the lower aromatic fuels. Similar to PM mass, both total and solid particle number emissions demonstrated an upward trend for the high PMI fuels with an increase in ethanol content. While the study is consistent with other studies showing that increasing aromatics and PMI values lead to higher PM emissions, the results also suggest that this relationship is complicated by the presence of varying levels of ethanol in high aromatic and PMI fuels, where increasing levels of ethanol in these fuels can also lead to PM increases. High molecular weight and low volatility hydrocarbon species (especially aromatics) also strongly impacted particulate emissions formation in GDI vehicles.